2012
DOI: 10.1002/anie.201203767
|View full text |Cite
|
Sign up to set email alerts
|

A Multicolor Nanoprobe for Detection and Imaging of Tumor‐Related mRNAs in Living Cells

Abstract: Multidetector: A novel nanoprobe, based on multicolor nanoflares, for the simultaneous detection and imaging of three tumor‐related mRNAs in living cells has been developed. The nanoprobe possesses high specificity, nuclease stability, and good biocompatibility. It can also effectively distinguish cancer cells from normal cells and identify changes in the levels of mRNA expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
250
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 307 publications
(258 citation statements)
references
References 42 publications
4
250
1
Order By: Relevance
“…4, even with concentrations as high as 1.0 Â 10 À 11 M of actin mRNA, let7a, let-7e and let-7f, signals were not more than 10% relative to those toward the case of target survivin mRNA. This high specificity is much better than those of previously reported mRNA biosensors (Li et al, 2012), due to the mismatch discrimination ability of the DSN (Table S2).…”
Section: Selectivity Of the Sensing Strategymentioning
confidence: 59%
“…4, even with concentrations as high as 1.0 Â 10 À 11 M of actin mRNA, let7a, let-7e and let-7f, signals were not more than 10% relative to those toward the case of target survivin mRNA. This high specificity is much better than those of previously reported mRNA biosensors (Li et al, 2012), due to the mismatch discrimination ability of the DSN (Table S2).…”
Section: Selectivity Of the Sensing Strategymentioning
confidence: 59%
“…Hybridization tests were carried out in solutions spiked with a mixture of three targets, and the nanoscale MBs respond only to the specific target with negligible crosstalk. Since DNAAuNP conjugates show highly efficient cellular uptake, later Li et al [105] demonstrated a multicolor fluorescence nanoprobe based on nanoflares, that can simultaneously detect and image three intracellular tumor-related mRNAs in living cells. The fluorescence intensity was found to correlate well with the concentration of tumor-related mRNA in living cells, which provides a useful means to monitor the stage of tumor progression.…”
Section: Engineering Of Nano-surfaces With Dna Nanostructuresmentioning
confidence: 99%
“…Among these, the gold-based nanoparticles are highly preferable for bioimaging and therapeutic applications due to their remarkable optical properties, high photothermal conversion efficiency, and easy surface functionalization (Govorov and Richardson 2007;Li et al 2012;Zhang et al 2014). It is worth noting that the localized surface plasmon resonance (LSPR) properties of gold nanoparticles depend heavily on their shape, size, and structures (Jones et al 2011;Nehl and Hafner 2008).…”
Section: Introductionmentioning
confidence: 99%